Prevalence of Hymenolepis nana in children in Baghdad- Al-Resafa: Alia Y. Yakoob , Afkar M. Hadi - Yakoob, Alia Y. (The Iraqi Journal of Veterinary Medicine, 2009)
From March to November 2004 a total of 634 stool samples from the children coming to thehospitals, cure centers and randomly from the children of kindergarten and primary schools. Generalstool examination and precipitation methods were performed on each specimen, the infection rate ofHymenolpes nana 1.8% among children for both Gender(male and female) for different ages that hadbeen recorded the highest rate for (4- 6)year is 2.94% and the lowest rate for (9-12)year is 1.4%.Seasonal variation were discussed, that August was recorded the highest rate 5.8%.